Revisiting the effect of mobile advertising content on buying intention / Nor Hazlina Hashim, Normalini Md Kassim and Roshni Ann George - Hashim, Nor Hazlina; Md Kassim, Normalini; George, Roshni Ann (Universiti Teknologi MARA Cawangan Pahang, 2017)
The digital era is known for technological breakthroughs in knowledge exchange through portable computing devices that include android and iOS smart phones. These gadgets, which have become a necessity for many, offer numerous advertising opportunities for companies to reach a wide pool of potential customers. Mobile advertising holds the best promise for one-to-one communication and provides avenues for direct and personalised marketing. Previous studies on consumer attitudes towards mobile advertising have generated conflicting results. This paper conceptualizes the effect of mobile advertising content on buying intention in a framework derived from past models and theories of technology acceptance. In light of the high purchase intentions of the younger generation in Malaysia, antecedents previously used in predicting the behavioural response of consumers towards mobile advertising and purchase intention were reexamined and combined with the personalization factor. Additionally, subjective norms and perceived behavioural control are proposed to have considerable impact on the purchase intentions of consumers in Malaysia. It is hoped that the proposed framework will lead to further clarity about the importance of mobile advertising content on behavioural response and therefore benefit the marketing efforts of companies by providing valuable insights on factors that influence the buying intentions of Malaysian consumers.